Measuring College Success for International Baccalaureate Diploma and Certificate Candidates - Hill, Jennifer Coles (Journal of International Students, 2018)
This quantitative study was conducted at a private international high school. The study purpose was to investigate United States college trends comparing International Baccalaureate Diploma Program candidates and International Baccalaureate Non-Diploma Program candidates from the same school in Asia. Data was collected for the Classes of 2007-2012 and the two groups were compared based on the number of college acceptances and the eventual collegiate success of the two groups once they matriculated to college, as measured by college persistence and graduation rates. The information analyzed provides data to explore the final educational outcomes for IB graduates and determine if there is a significant difference in the college success of the two groups.